Parallel evaluation of interaction nets with MPINE - Pinto, Jorge Sousa (2001)
We describe the MPINE tool, a multi-threaded evaluator for Interaction Nets. The evaluator is an implementation of the present author's Machine for Interaction Nets and uses POSIX threads to achieve concurrent execution. When running on a multi-processor machine (say an SMP architecture), parallel execution is achieved effortlessly, allowing for desktop parallelism on commonly available machines.